2024
DOI: 10.1088/1475-7516/2024/03/002
|View full text |Cite
|
Sign up to set email alerts
|

An exact model for enhancing/suppressing primordial fluctuations

Guillem Domènech,
Gerson Vargas,
Teófilo Vargas

Abstract: Enhancements of primordial curvature fluctuations in single field inflation often involve departures from attractor trajectories in the phase space. We study enhancement/suppression of primordial fluctuations in one of the simplest models with exact background solutions for arbitrary initial conditions: a single field inflationary model with a piecewise exponential potential. We then present close to exact analytical solutions for primordial fluctuations in a general transition between two slow-roll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 171 publications
1
2
0
Order By: Relevance
“…While this work was in preparation ref. [96] appeared, where it was shown that the usual δN formalism could only be applied sufficiently long after a sudden transition, such that δϕ h is dominated by the growing mode, which is consistent with our results.…”
Section: Jcap05(2024)053supporting
confidence: 92%
“…While this work was in preparation ref. [96] appeared, where it was shown that the usual δN formalism could only be applied sufficiently long after a sudden transition, such that δϕ h is dominated by the growing mode, which is consistent with our results.…”
Section: Jcap05(2024)053supporting
confidence: 92%
“…The detection of gravitational waves (GWs) from a binary black hole merger by the LIGO-Virgo collaboration has brought attention to the PBHs (Abbott et al 2016a(Abbott et al , 2016b(Abbott et al , 2016c(Abbott et al , 2017a(Abbott et al , 2017b(Abbott et al , 2017c(Abbott et al , 2017d. PBHs could be considered as a suitable candidate for explaining all or a portion of the dark matter in the Universe (Hawking 1971;Chapline 1975;Polnarev & Khlopov 1985;Ivanov et al 1994;Capozziello & Faraoni 2010;Capozziello & De Laurentis 2011;Nojiri & Odintsov 2011;Olmo 2011; De la Cruz-Dombriz & Sáez-Gómez 2012; Choudhury & Mazumdar 2014;Nojiri et al 2017;Hajkarim & Schaffner-Bielich 2020;Solbi & Karami 2021a;Teimoori et al 2021b;Solbi & Karami 2021b;Cai & Piao 2021;Chakraborty et al 2022;Papanikolaou et al 2022;Rezazadeh et al 2022;Papanikolaou et al 2023b;Choudhury et al 2023b;Papanikolaou et al 2023a;Cai et al 2023;Domènech et al 2024). Since PBHs originate from the gravitational collapse of primordial density perturbations, they are not subject to the Chandrasekhar mass limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative mechanisms within the framework of single-field inflation have also been proposed to alleviate problematic fine-tuning [41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Mechanisms involving steplike features in potentials have been studied [41,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%